(untitled) (Research, Society and Development, 2023)
The objective of the present study was to evaluate the physiological responses in soybean seeds with different vigor levels treated with polymers and thiamethoxam subjected to simulated water deficit. Two lots of soybean seeds from the Nidera NA5909 cultivar were used, in which differentiation occurred based on their vigor level. To carry out the seed treatment, the commercial product Cruizer 350FS was used, due to its active ingredient thiamethoxam having the bioactivating property and the polymers Laborsan and Likoseed were used. The simulated water stress condition was carried out in two ways, on rolls of germitest paper, which was carried out using polyethylene glycol solutions (PEG 6000) and on PVC trays, containing sand and different levels of water saturation. The evaluation of physiological quality was carried out through germination tests, first germination count, length and dry mass of seedlings. It was concluded that for both batches, both the water stress simulated in paper rolls and in sand, there was a reduction in the physiological performance of the seeds and that the molecule thiamethoxam associated or not with polymers provided better development in low vigor soybean seedlings when subjected to water stress.